Amyloid and tau pathologies associate with distinct aspects of the inflammatory cascade. (20th December 2022) - Bellaver, Bruna; Leffa, Douglas Teixeira; Ferreira, Pamela C.L.; Ferrari‐Souza, João Pedro; De Bastiani, Marco Antônio; Tissot, Cécile; Lussier, Firoza Z; Therriault, Joseph; Benedet, Andréa Lessa; Servaes, Stijn; Chamoun, Mira; Stevenson, Jenna; et al.
Abstract: Background: Inflammation has long been pointed out as a key feature in Alzheimer's disease (AD). However, the heterogeneity of AD pathology might trigger different aspects of the immune response. Here, we aimed to study the association of the newly proposed concept of inflammatory composite indexes with Aβ and tau pathologies across the aging and AD spectra. We hypothesize that distinct inflammatory pathways are associated with the different hallmarks of AD. Method: A panel of 92 inflammation‐related markers was measured in the CSF of 60 individuals (35 cognitively unimpaired and 25 cognitively impaired) from the McGill TRIAD cohort. These 92 proteins were clustered by ontogenetic similarity and physical interaction using STRING. A z‐scored composite value representing each cluster was created for each individual. Individuals were classified as Aβ‐ and tau‐positive using global [ 18 F]AZD4694 and temporal meta‐ROI [ 18 F]MK6240 PET, respectively. Linear regressions (corrected by diagnosis, age, sex, and APOEɛ4 status) and receiver operating characteristic (ROC) analyses evaluated clusters' performance. Result: Of the six clusters identified in our protein network analysis, three positively correlated with global Aβ‐PET (C4, C5, and C6) and three with meta‐ROI tau PET (C2, C4, and C5;Fig.1 ). However, controlling for Aβ PET, tau PET was only associated with C2, indicating that the association with the other two clusters (C4 and C5) was dependent of Aβ pathology. The cluster exclusively associated with tau (C2), represents tumor necrosis factor‐mediated signaling pathways. On the other hand, C6, related to the stimulation of interferon‐gamma production, and C5, related to glial cell‐derived neurotrophic receptor binding, are exclusively associated with Aβ. ROC analysis showed that all clusters presented a better performance predicting Aβ‐PET positivity than tau‐PET positivity (Fig.2A, B ). Additionally, overall the clusters showed a better performance than sTREM2, a classical inflammatory biomarker. Conclusion: Our novel clustering approach supports that Aβ and tau proteinopathies are associated with distinct aspects of the inflammatory cascade. Our results suggest that a composite of inflammatory proteins better identifies AD pathology than a single marker. Finally, this suggested cluster approach helps to understand the inflammatory response to Aβ and tau and can uncover inflammation‐related AD pathways.